Application of Rainfall Data in Drought Hazard Prediction in The Bengawan Solo River Basin Using The Rainfall Anomaly Index (RAI) and Standardized Precipitation Index (SPI) - Nikmah, Norma Wihdatun; Yakan, Annisa Fathi; Rahima, Ahdania (Universitas Muhammadiyah Surakarta, 2024)
This study investigates the impact of the Southern Oscillation Index (SOI) on meteorological droughts in the Bengawan Solo River Basin, Indonesia, from 2004 to 2023. Indonesia’s climate is influenced by the El Niño Southern Oscillation (ENSO), with negative SOI values (El Niño conditions) linked to drought events and positive values associated with the rainy season. This study analyzed the values of multiple stations' Rainfall Anomaly Index (RAI) and Standardized Precipitation Index (SPI). This study evaluates the compatibility of drought indices obtained from the Rainfall Anomaly Index (RAI) and the Standardized Precipitation Index (SPI) with the Southern Oscillation Index (SOI). The study's results indicate that the drought index using the Standardized Precipitation Index (SPI) method yields a higher percentage of compatibility with the Southern Oscillation Index (SOI), averaging 60.78%. The compatibility of the SPI method can also be observed in the number of meteorological dry months during 2010, the year of the most severe La Niña, and in 2015, during the most severe El Niño. Through the SPI method, it can also be demonstrated that rainfall data can accurately reflect drought events and rainy seasons, consistent with climate change occurrences.